Economic Aspects of Airport Security Systems (Behavioral Analysis) - Gechkova, Teodora; Kaleeva, Tiana (UNWE Yearbook, 2021)
The article presents different economic aspects of the implementation of non-verbal analysis programs and makes recommendations for their introduction in airport security, it outlines the opportunities for financial investment and the important issues to be taken into consideration. The aim of the research is to outline the importance of behavioral analysis in the field of airport infrastructure. The problematic area of this subject is provoked by the continuous increase of the risks and threats to the airport infrastructure and the necessity of modern and innovative methods to overcome them. In recent years, the non-verbal analyses have become more and more important for the economic, social and political relations, as well as for different aspects of security.
Keywords: Airport security; Security; Behavioral analysis; Economical